Creating hope in dystopia: Utopia as Method as social pedagogy in early childhood studies. Issue 1 (28th February 2023) - Gallagher, Stuart; Stobbs, Nicola
Abstract : Those who choose to engage with the academic world of early childhood are frequently caught between encouraging students to advocate for children and contribute to the construction of a good life and navigating the regulatory frameworks that shape future practice. In short, we must prepare students for the highly skilled work of supporting people who live their lives in day-to-day actions that are underpaid, under-resourced and overlooked. Those who prepare students for this reality are tasked with developing programmes that both instil hope and pragmatism that will sustain them when faced with these everyday realities. This article outlines how the authors addressed this through an adapted use of Utopia as Method in a module on an early childhood degree. By following its distinct modes, students are guided to position themselves not as passive observants of a childhood that is socially constructed around them, but as social and political actors engaged with making human beings human. Among other issues the article evaluates the intersection between social pedagogy, utopia and the future of early childhood. Based on explorations undertaken for this article, we argue that the imaginative reconstruction of childhood through higher education is at ease with the values and purpose of social pedagogy. We reflect that, while the method employed as part of a module was useful in terms of personal development and future-oriented practice, the need to include children's voices is yet to be developed.